Investigating the Relationship Between Prosocial Rule Breaking and Quality of Life with the Mediating Role of Psychological Safety Among Women Employed in Government Offices in Ahvaz - Latifat , Fatemeh; Naami, Abdozahra; Hashemi , Seyed Esmaeil (Psychology of Woman Journal, 2026)
Objective: The present study aimed to investigate the relationship between prosocial rule breaking and quality of life with the mediating role of psychological safety among women employed in governmental offices in Ahvaz. Methods and Materials: This study was applied in terms of purpose and descriptive-correlational in terms of methodology using structural equation modeling (SEM). The statistical population consisted of women employed in governmental offices in Ahvaz, from whom 385 participants were selected through convenience sampling. Data were collected using the Prosocial Rule Breaking Questionnaire developed by Vardaman et al. (2014), the World Health Organization Quality of Life Questionnaire–Short Form (WHOQOL-BREF), and Edmondson’s Psychological Safety Questionnaire. The collected data were analyzed using SPSS version 26 and AMOS version 25. Descriptive statistics, Pearson correlation coefficients, and structural equation modeling were employed to examine the relationships among the research variables and test the conceptual model. Findings: The results revealed significant positive relationships among prosocial rule breaking, psychological safety, and quality of life. Prosocial rule breaking had a positive and significant effect on psychological safety (β = .580). Psychological safety also demonstrated a positive and significant effect on quality of life (β = .390). In addition, the direct effect of prosocial rule breaking on quality of life was positive and significant (β = .230). The indirect effect of prosocial rule breaking on quality of life through psychological safety was confirmed (β = .226), indicating the mediating role of psychological safety in this relationship. The structural model demonstrated a desirable fit with the data (χ²/df = 2.38, CFI = .951, RMSEA = .060). Furthermore, prosocial rule breaking explained 33.6% of the variance in psychological safety, while prosocial rule breaking and psychological safety together explained 41.2% of the variance in quality of life. Conclusion: The findings suggest that prosocial rule breaking, when occurring within psychologically safe organizational environments, can contribute positively to employees’ quality of life. Psychological safety plays a significant mediating role by reducing fear of negative consequences and encouraging constructive organizational behaviors. Therefore, creating supportive and psychologically secure workplace climates may enhance employees’ well-being, organizational participation, and adaptive performance among women employed in governmental organizations.